Src Family Kinases Regulate Interferon Regulatory Factor 1 K63 Ubiquitination following Activation by TLR7/8 Vaccine Adjuvant in Human Monocytes and B Cells - Tulli, Lorenza; Cattaneo, Francesca; Vinot, Juliette; Baldari, Cosima T.; D’Oro, Ugo (Frontiers in Immunology, 2018)
Toll-like receptors (TLRs) play a key role in the activation of innate immune cells, in which their engagement leads to production of cytokines and co-stimulatory molecules. TLRs signaling requires recruitment of toll/IL-1R (TIR) domain-containing adaptors, such as MyD88 and/or TRIF, and leads to activation of several transcription factors, such as NF-κB, the AP1 complex, and various members of the interferon regulatory factor (IRF) family, which in turn results in triggering of several cellular functions associated with these receptors. A role for Src family kinases (SFKs) in this signaling pathway has also been established. Our work and that of others have shown that this type of kinases is activated following engagement of several TLRs, and that this event is essential for the initiation of specific downstream cellular response. In particular, we have previously demonstrated that activation of SFKs is required for balanced production of pro-inflammatory cytokines by monocyte-derived dendritic cells after stimulation with R848, an agonist of human TLRs 7/8. We also showed that TLR7/8 triggering leads to an increase in interferon regulatory factor 1 (IRF-1) protein levels and that this effect is abolished by inhibition of SFKs, suggesting a critical role of these kinases in IRF-1 regulation. In this study, we first confirmed the key role of SFKs in TLR7/8 signaling for cytokine production and accumulation of IRF-1 protein in monocytes and in B lymphocytes, two other type of antigen-presenting cells. Then, we demonstrate that TLR7 triggering leads to an increase of K63-linked ubiquitination of IRF-1, which is prevented by SFKs inhibition, suggesting a key role of these kinases in posttranslational regulation of IRF-1 in the immune cells. In order to understand the mechanism that links SFKs activation to IRF-1 K63-linked ubiquitination, we examined SFKs and IRF-1 possible interactors and proved that activation of SFKs is necessary for their interaction with TNFR-associated factor 6 (TRAF6) and promotes the recruitment of both cIAP2 and IRF-1 by TRAF6. Collectively, our data demonstrate that TLR7/8 engagement leads to the formation of a complex that allows the interaction of cIAP2 and IRF-1 resulting in IRF-1 K63-linked ubiquitination, and that active SFKs are required for this process.